Structural Constraints of Vaccine-Induced Tier-2 Autologous HIV Neutralizing Antibodies Targeting the Receptor-Binding Site - Bradley, Todd; Fera, Daniela; Bhiman, Jinal; Eslamizar, Leila; Lu, Xiaozhi; Anasti, Kara; Zhang, Ruijung; Sutherland, Laura L.; Scearce, Richard M.; Bowman, Cindy M.; Stolarchuk, Christina; Lloyd, Krissey E.; et al. (Cell reports (Cambridge), 2016)
Antibodies that neutralize autologous transmitted/founder (TF) HIV occur in most HIV-infected individuals and can evolve to neutralization breadth. Autologous neutralizing antibodies (nAbs) against neutralization-resistant (Tier-2) viruses are rarely induced by vaccination. Whereas broadly neutralizing antibody (bnAb)-HIV-Envelope structures have been defined, the structures of autologous nAbs have not. Here, we show that immunization with TF mutant Envs gp140 oligomers induced high-titer, V5-dependent plasma neutralization for a Tier-2 autologous TF evolved mutant virus. Structural analysis of autologous nAb DH427 revealed binding to V5, demonstrating the source of narrow nAb specificity and explaining the failure to acquire breadth. Thus, oligomeric TF Envs can elicit autologous nAbs to Tier-2 HIVs, but induction of bnAbs will require targeting of precursors of B cell lineages that can mature to heterologous neutralization. [Display omitted] •HIV-1 TF Env immunization induced potent Tier-2 neutralizing antibodies (nAbs)•Vaccine-elicited nAbs target CD4bs and mimic autologous nAbs in infected individual•Autologous nAb-Env complex structure reveals mechanism of strain-specific neutralization HIV-1 vaccine elicitation of antibodies against neutralization-resistant (Tier-2) viruses is rare. Bradley et al. demonstrate induction of antibodies that can neutralize a vaccine-matched Tier-2 virus in a rhesus macaque immunized with HIV trimers isolated from a HIV-1-infected individual. Structural analysis revealed the mechanism of restricted neutralization breadth.